Імітаційне моделювання тягово-динамічних показників тракторів на основі польових випробувальних циклів PowerMix - Ребров, Олексій Юрійович; Кальченко, Борис Іванович; Якунін, Максим Євгенович; Реброва, Олена Михайлівна; Артюшенко, Олександр Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2021)
В роботі наведена математична модель для визначення тягово-динамічних показників тракторів з використанням польових випробувальних циклів PowerMix. Запропонований план імітаційного експерименту, який враховує розподіл річного обсягу весняних та літньо-осінніх робіт трактора за типовими сільськогосподарськими операціями, а також розроблена методика наведення результатів імітаційного моделювання до показників базового трактора потужністю 100 кВт, що дає змогу порівнювати трактори довільних схемних рішень і потужності. В якості прикладу наведені результати моделювання показників трактора New Holland T6.180.

The paper presents a mathematical model for determining the traction and dynamic performance of tractors using PowerMix field test cycles. The mathematical model was successfully tested, during which a set of traction-dynamic parameters of a wheeled tractor with the maximum discrepancy on individual indicators relative to experimental data, which is -8.4… + 7.9%. A plan of a simulation experiment is proposed, which takes into account the distribution of the annual volume of spring and summer-autumn tractor work by typical agricultural operations, and includes loading traction cycles with power take-off through PTO and hydraulic system of the tractor. To assess the efficiency of tractors based on a set of traction-dynamic indicators obtained from field PowerMix test cycles, developed a method of bringing the simulation results to the performance of the base tractor with a capacity of 100 kW, which corresponds to the basic cycles PowerMix. The technique makes it possible to compare tractors of arbitrary design solutions and power. As an example, the results of modeling the traction and dynamic performance of the New Holland T6.180 tractor on PowerMix field test cycles determined the average values of productivity and per hectare of fuel consumption plowed by the base tractor, which are 1,239 ha / h and 14.58 kg / ha, respectively.
Simulation modeling of traction and dynamic indicators of tractors on the basis of PowerMix field cycles test
Keywords: трактор; PowerMix; математична модель; імітаційний експеримент; tractor; PowerMix; mathematical model; simulation experiment